Analisis Rasio Profitabilitas pada Laporan Keuangan Perusahaan - Rifky Septianda Wijaya; Erni Intan Permata Sari; Finda Findiana (STEBI Global Mulia Cikarang, 2024)
The assessment of a company's financial level can be done by analyzing the company's financial statements. To find out whether the company's financial condition is in good condition, various analyses can be carried out, one of which is a ratio analysis. One of the tools to assess financial performance is the Profitability Ratio analysis which aims to measure the effectiveness of overall management aimed at the size of the level of profit obtained. The better the profitability ratio, the better the profitability of a company. The purpose of calculating financial ratios is needed for a company to be able to find out the good and bad financial conditions in the processing of a company. Financial statements prepared by a company can be used as an internal managerial decision-making tool as well as for external parties of the company. With the analysis of the financial statements, it can be known the state and development of the company that has been achieved by the company in the past and in the current time, both private enterprises and state-owned enterprises. In this study, the researcher used a case study method where the researcher read and summarized the profitability ratio that had been carried out by previous researchers.